Actin‐related protein 5 suppresses the cooperative activation of cardiac gene transcription by myocardin and MEF2. Issue 2 (12th January 2023) - Morita, Tsuyoshi; Hayashi, Ken'ichiro
Abstract : MYOCD is a transcription factor important for cardiac and smooth muscle development. We previously identified that actin‐related protein 5 (ARP5) binds to the N‐terminus of MYOCD. Here, we demonstrate that ARP5 inhibits the cooperative action of the cardiac‐specific isoform of MYOCD with MEF2. ARP5 overexpression in murine hearts induced cardiac hypertrophy and fibrosis, whereas ARP5 knockdown in P19CL6 cells significantly increased cardiac gene expression. ARP5 was found to bind to a MEF2‐binding motif of cardiac MYOCD and inhibit MEF2‐mediated transactivation by MYOCD. RNA‐seq analysis revealed 849 genes that are upregulated by MYOCD‐MEF2 and 650 genes that are repressed by ARP5. ARP5 expression increased with cardiomyopathy and was negatively correlated with the expression of Tnnt2 and Ttn, which were regulated by cardiac MYOCD‐MEF2. Overall, our data suggest that ARP5 is a potential suppressor of cardiac MYOCD during physiological and pathological processes. Abstract : We found that the overexpression of ARP5 in the murine hearts leads to cardiac hypertrophy and fibrosis. ARP5 binds to the MEF2‐binding motif (MBM) of cardiac MYOCD and inhibits the interaction between MYOCD and MEF2, thereby suppressing cardiac gene expression. ARP5 is highly expressed in fetal and failing hearts, suggesting the developmental and pathological importance of ARP5 in the cardiovascular system.